The Media, Groundwater, and Development: Scientific Input in the Arizona Daily Star, 2006 - Christopher, David (My University, 2008)
In 2006, the Arizona Daily Star, a newspaper based in Tucson, Arizona, paid significant attention to groundwater issues. Authors at the Star discussed groundwater and its connections to commercial, residential, and industrial development, highlighting the tensions between scientists and developers. Based on a wide body of literature about the media’s use of science and public perceptions of science, the newspaper validated the mass media’s tendency to construct arguments that are more attuned to generating resonance with the readership than they are to discussing scientific facts. By skewing expertise, offering limited explanations of scientific terms and processes, and portraying science as uncertain and conflictual, authors at the Star reaffirm common perceptions about the necessity of growth for political and economic reasons.
Keywords: Groundwater; Media; Development; Public perception